Theta Oscillations and Source Connectivity During Complex Audiovisual Object Encoding in Working Memory - Xie, Yuanjun; Li, Yanyan; Duan, Haidan; Xu, Xiliang; Zhang, Wenmo; Fang, Peng (Frontiers in Human Neuroscience, 2021)
Working memory is a limited capacity memory system that involves short-term storage and processing of information. Studies on working memory mostly focus on the essential roles of neural oscillations during item encoding from single sensory modalities (e.g., vision and audition). However, the characteristics of neural oscillations during multisensory encoding in working memory is rarely studied. In this study, we investigated the oscillation characteristics of neural signals in scalp electrodes and mapped functional brain connectivity while participants encoded complex audiovisual objects in a working memory task. Experimental results showed that theta oscillations (4–8 Hz) were prominent and topographical distributions were across multiple cortical regions, including prefrontal (e.g., superior frontal gyrus), parietal (e.g., precuneus), temporal (e.g., inferior temporal gyrus), and occipital (e.g., cuneus) cortices. Furthermore, neural connectivity at the theta oscillation frequency was significant in these cortical regions during audiovisual object encoding compared with single modality object encoding. We thus suggest that local oscillations and interregional connectivity via theta activity play an important role during audiovisual object encoding and may contribute to formation of working memory traces from multisensory items.